RELATIONSHIPBETWEENBACTERIAANDFUNGINUMBER IN RHIZOSPHERE AND BULK SOIL. - Mowafaqn Sultan; Marwan Yassen (Mesopotamia Journal of Agriculture)
Pot experiment was conducted in a Plastic house to study the number and percentage of bacteria and fungi in Rhizosphere (RS) and Bulk Soil (BS) using four types of crops, (wheat, onions, faba bean, clover) has been cultivated in silty clay loam soil from AL-​​Rashidiya farm, Soil Samples were collected to estimated the bacteria, fungi numbers, and soil reaction in two stages of plant growth (60 day,120 days). Results showed: studying the number and percentage of bacteria and fungi in Rhizosphere and Bulk Soil using the four types of crops which had been cultivated in silty clay loam soil from Al-​​Rashidiya site, Samples of the soil were took to estimated the bacteria, fungi, and soil reaction in  two phases of stages of plant growth (60 days, 120 days). The Results  showed that the number and percentage of bacteria and fungi in (RS) was increasing compared to bacteria and fungi in (BS) and in  all soils cultivated with the crops in the two stages of growth  (60 days, 120 days). Faba bean (442.4*105UCF) and wheat (434.7*105UCF) at the first stage of growth (60 days)were the highest increasing in the number of bacteria in(RS) compared with the number of bacteria in (BS), with the increase (1172.7،1139.1 %) and ratios (R/S) amounted to (1:12.7، 1:12.3) respectively, In the second stage of growth (120 day of planting) there was a significant increase in bacteria number  in)RS(soil and for all crops compared to the)BS(and the highest increase was in soil planted with wheat (378.9*105UCF) clover (350.1*105UCF) with increase of (1051.3 ,898.93%) and rates (RS) amounted to (1:11.5, 1:9.9), respectively Also that the number of fungi have achieved a significant increase in the (RS)  compared to (BS) and the highest increase of fungi in the (RS) was in the soil cultivated with faba bean, followed in the soil cultivated increase of (36.88*103UCF) and rates (R/S) was (1:1.3). In the second stage of growth (120 day of planting) there was a significant increase in fungi in)RS(achieved a significant increase compared to the)BS(soil and the highest increase was in the in the soil planted with clover ,faba bean and an increase of (R/S) was (34.87, 34.76*103 UCF) and the rate of (1:1.23،1:30) respectively. The soil reaction RS and BS was affected in both stage with rate degrees (0.13, 0.11) in RS and BS with (1.68,1.42%) respectively compared to control.